Apollo e Marsia - Impett, Jonathan (Lausanne, Switzerland EPFL, 2024)
This work expands the moment in time represented in Tintoretto’s painting, La gara tra Apollo e Marsia (c.1545). Apollo, playing a viola da braccio with sympathetic strings, has been chal¬lenged by the satyr Marsia, playing a long wind instrument, to see who is the greater musician. Based on Ovid’s Metamorphoses Apollo will win, but in the moment depicted the two protago¬nists are waiting for the judgement of King Midas. Apollo e Marsia is an installation con¬sisting of two large screens displaying performances of compositions for viola d’amore and alto flute in changing patterns of fragments. The viola sound is processed through two long tubes, the flute through two long strings as their performances modu¬late each other. In addition, both are constantly listening to each other and to changing sounds in the room through machine learning networks, generating new memories that may predict, remind or surprise. The piece is therefore a play on the nonlinearity of memory under stress; moments are recalled, replayed or intrude, but are always changing in their recon¬struction. Apollo and Marsia listen to each other, trying to second-guess the other’s memory. At their root, these sonic memories all derive from two hymns to Apollo inscribed in stone at the temple dedicated to him in Delphi. Arguably the earliest remain¬ing instances of music notation, and likewise fragmented by erasures, these hymns embody partially-lost memory that we attempt to reconstruct.
Exhibition 'Musica ex Machina', 20/09/24 - 26/06/25
FRIS
1
Keywords: Music, Thought and Technology